2008
DOI: 10.1111/j.1440-6055.2008.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of four field populations of the diamondback moth Plutella xylostella L. (Lepidoptera: Yponomeutidae) to six insecticides in the Sydney region, New South Wales, Australia

Abstract: Concerns about the failure of insecticides to control the diamondback moth (DBM) Plutella xylostella in the Sydney region of New South Wales, Australia, necessitated the current investigation to establish the susceptibility of four field populations of the DBM to six insecticides. These include two each of organophosphates (OPs), and synthetic pyrethroid insecticides as well as two new products with different modes of action, spinosad and indoxacarb, currently recommended for DBM control in the region. Topical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Eziah et al (2008) verified that Australian field populations of P. xylostella were susceptible to spinosad. In the present study, although five populations had toxicity ratios to spinosad (2.3 -to 5.1 -fold), both field and laboratory populations sur- Chi Square (p > 0.05).…”
mentioning
confidence: 66%
“…Eziah et al (2008) verified that Australian field populations of P. xylostella were susceptible to spinosad. In the present study, although five populations had toxicity ratios to spinosad (2.3 -to 5.1 -fold), both field and laboratory populations sur- Chi Square (p > 0.05).…”
mentioning
confidence: 66%
“…Sial et al (2011d) suggested enhanced esterase activity is responsible for the resistance to chlorantraniliprole in C. rosaceana. Enhanced activity of GST sand MFO enzymes has been found to be related to pyrethroid, organophosphate resistance (Eziah et al, 2008;Ashraf et al, 2010;Tang et al, 2011). Di et al (2014) reported that detoxification by mixed-function oxidase and glutathione S-transferases might be involved in chlorantraniliprole resistance in P. xylostella.…”
Section: Discussionmentioning
confidence: 97%
“…The results obtained from this bioassay indicated that indoxacarb is also toxic to P. xylostella collected in Tehran. Toxicity of indoxacarb on P. xylostella was reported by Eziah et al (2008). Sayyed et al (2005) tested the effect of several insecticides, including indoxacarb, on a number of generations of P. xylostella in the laboratory, and LC 50 values were estimated as 40 and 3 lg L -1 for the 2nd and 8th generations, respectively.…”
Section: Toxicity Of Indoxacarbmentioning
confidence: 99%